A300 DIET-MICROBIOTA INTERACTIONS UNDERLIE SYMPTOMS IN IBS. (1st March 2018) - De Palma, G; Reed, D E; Pigrau, M; Lu, J; Sidani, S; Zhang, Y; YU, Y; Jiménez-Vargas, N N; Sessenwein, J; Lopez Lopez, C D; Polanco, J O Jaramillo; Verdu, E; et al.
Abstract: Background: The mechanisms underlying IBS are poorly understood but growing evidence suggests that immune activation and the microbiota may be involved. We recently demonstrated that a diet low in fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) improves symptoms in IBS patients and this is correlated with decreased mast cell activation and changes in the microbiota composition. Thus, FODMAPs may be a useful tool to evaluate IBS mechanisms. Aims: To investigate the interplay of host's gut function, intestinal microbiota and immune factors in response to FODMAPs in the humanized IBS mouse model. Methods: Germ-free NIH Swiss mice were colonized with fecal microbiota from two IBS patients (non-constipation) with a high (P1) or low (P2) urinary histamine level (n=20 mice /patient), suggesting differing levels of immune activation. Mice were assigned to a custom-made low or high FODMAP diet (LF and HF, respectively). Three weeks later, GI transit (beads study), cecal volume (CT scan) and intestinal permeability (FITC-Dextran) were assessed. Animals were then euthanized and neuronal excitability assessed by patch clamp recordings of DRG neurons (action potential rheobase) exposed to colonic supernatants and changes in mechanosensitivity of single unit afferent recordings in mouse distal colon from mice receiving LF or HF diets. Results: P1 mice receiving a HF diet had slower GI transit (p=0.02), increased cecal volume (p=0.004), indicative of increased gas content, increased permeability (FITC-Dextran: p=0.04), and lower weight gain (p=0.04) compared to P1 mice on a LF diet. In electrophysiological studies, the rheobase was decreased (24%; p=0.003) and mechanosensitivy increased (p=0.06) in the HF compared to the LF mice. The decreased rheobase was blocked by a H1 or a PAR2 antagonist. In contrast, P2 mice receiving the HF diet displayed modest increase in cecal volume (p=0.02) but no differences in GI transit, permeability or weight compared to those on the LF diet. The rheobase was modestly decreased (17%, p<0.05) but no changes were found in mechanosensitivity. Conclusions: Fermentable carbohydrates cause changes in GI function that likely underlie symptoms of IBS, and the magnitude of these functional changes is determined by gut microbiota. Our data suggests the microbiota-diet interactions play a key role in IBS pathogenesis and symptom generation. First two authors contributed equally to this work. Funded by grants from CIHR and CAG. Funding Agencies: CAG, CIHR